Architectural Dependency Analysis: Addressing the Elephant in the Room. - Sangwan, Raghvinder S.; Nord, Robert L.; Ozkaya, Ipek (Computer (00189162), 2021)
Dependency analysis is typically limited to the static analysis of code structures. We applied this practice to safety-critical systems that were re-engineered to reduce safety testing and technology upgrade cost. We discuss the need for a well-defined description of architectural dependencies to address the observed gaps.